An analytic spin chain model with fractional revival. (8th July 2016) - Lemay, Jean-Michel; Vinet, Luc; Zhedanov, Alexei
Abstract: New analytic spin chains with fractional revival are introduced. Their nearest-neighbor couplings and local magnetic fields correspond to the recurrence coefficients of para-Racah polynomials which are orthogonal on quadratic bi-lattices. These models generalize the spin chain associated to the dual-Hahn polynomials. Instances where perfect state transfer also occurs are identified.